2020
DOI: 10.1002/jpen.1868
|View full text |Cite
|
Sign up to set email alerts
|

Early Lipid Intake Improves Cerebellar Growth in Very Low‐Birth‐Weight Preterm Infants

Abstract: Background Despite recent advances in nutrition practice in the neonatal intensive care unit, infants remain at high risk for growth restriction following preterm birth. Additionally, optimal values for macronutrient administration, especially lipid intake, have yet to be established for preterm infants in the extrauterine environment. Methods We studied preterm infants born at very low‐birth weight (VLBW, <1500 g) and ≤32 weeks’ gestation. Cumulative macronutrient (carbohydrate, lipid, protein, energy) intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
2
10
2
Order By: Relevance
“…Our results linking energy intake and brain size are consistent with several [ 13 , 14 , 15 ]—though not all [ 16 , 17 , 38 ]—prior studies of macronutrient intake and brain development in preterm infants. Among three prior studies that reported positive associations between macronutrient intake and brain volumes [ 13 , 14 , 15 ], all found that energy intake was linked to brain size, but varied in the brain region involved, with the most common regions being the cerebellum [ 13 , 14 , 15 ], basal ganglia [ 13 , 14 ], and total brain volume [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results linking energy intake and brain size are consistent with several [ 13 , 14 , 15 ]—though not all [ 16 , 17 , 38 ]—prior studies of macronutrient intake and brain development in preterm infants. Among three prior studies that reported positive associations between macronutrient intake and brain volumes [ 13 , 14 , 15 ], all found that energy intake was linked to brain size, but varied in the brain region involved, with the most common regions being the cerebellum [ 13 , 14 , 15 ], basal ganglia [ 13 , 14 ], and total brain volume [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results linking energy intake and brain size are consistent with several [ 13 , 14 , 15 ]—though not all [ 16 , 17 , 38 ]—prior studies of macronutrient intake and brain development in preterm infants. Among three prior studies that reported positive associations between macronutrient intake and brain volumes [ 13 , 14 , 15 ], all found that energy intake was linked to brain size, but varied in the brain region involved, with the most common regions being the cerebellum [ 13 , 14 , 15 ], basal ganglia [ 13 , 14 ], and total brain volume [ 14 ]. In contrast to energy, prior studies are inconsistent with respect to the relationship between protein intake and brain volume; some linked protein intake to the same regions as energy intake [ 13 , 14 ] while others found no relationship between protein intake and brain size [ 15 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Novel quantitative magnetic resonance imaging (MRI) techniquesincluding volumetric segmentation and diffusion tensor imaging-are emerging as noninvasive methods for evaluating the impact of early nutritional interventions on preterm brain development at the microstructural level [12]. Quantitative MRI has already been utilized to demonstrate the effects of early breast milk, macronutrient, and energy intake on preterm brain development by term-equivalent age, and could potentially be utilized as a future tool in determining ideal breast milk fortification practices [12,[82][83][84].…”
Section: Future Directionsmentioning
confidence: 99%